Sparky Enea with bust of John Steinbeck. - George A. Robinson (1913-1979. EFRR friend & personnel manager at California Packing Company from 1950-1972):::Creator::::::::::::
Horace 'Sparky' Enea, wearing a striped shirt and a sweater, stares at the bust of John Steinbeck.